Implementation of ANN with the Cyclical Order Method For Forecasting the Life Span of the World’s Population - Muhammad Rizal; Elviawaty Muisa Zamzami (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
This study aims to predict the age (life expectancy) of the world's population. This research is the development of research that has been done before. But in this study only to get the best architectural model to predict the age (life expectancy) of the world's population, using the Cyclical Order method. Whereas in this follow-up research, it will produce forecasting in the form of age (life expectancy) of the population in the world based on a model that has been obtained from previous research. The research data is the age data (life expectancy) of the world's population from the United Nations: